ANALYSIS OF BOAT BUILDING AGREEMENT BASED OF ISTISHNA' CONTRACT: A CASE STUDY IN SAWANG SOUTH ACEH - INDONESIA - Rahim, Ummi; Bukhari Ali; Yuhasnibar (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2024)
This study examines the transaction of boat building agreements in Sawang Ba'u village, Sawang sub-district, South Aceh district. The problem that wants to be studied in this paper is how the application of the istishna' contract in the practice of boat ordering agreements in the village of Sawang Ba'u, besides that the author wants to identify the problems that exist in the application of the istishna' contract in the boat manufacturing agreement in the village of Sawang Ba'u. To answer these problems, the author conducted field research and used a qualitative approach by collecting data through interviews, observation, and documentation. The main objective of this research is to see the application of the istishna' contract in boatbuilding transactions, as well as identify obstacles that may arise during the process of applying the contract. The results of this study are that in general the istishna' contract has gone well when viewed from the istishna' principles which include price agreements and clear specifications of goods. Then there are several obstacles in the implementation of the istishna' contract including the inaccuracy of the boat's construction time, the boat's durability when used for two to three months, but after the author conducted further interviews, these obstacles were caused by force majeure or events that occurred beyond human ability such as bad weather factors that made the boat's quality decrease and the boat's construction took a long time so that it did not damage or cancel the istishna' contract.